Le néofantastique : entre la transgression et l’esprit conservateur - Gadomska, Katarzyna (Romanica Silesiana)
The néofantastique (neo-fantasy) literature abounds in representations of transgressions, be it moral, religious, and social. This literary genre often deals with crimes, pornography, cannibalism, necrophilia, etc. Because the new fantasy literature breaks various cultural taboos, many critics perceive it as a genre liberal par excellence. However, there are also conservative, or didactic, works inscribed in the genre in which all transgressions are punished by the death of the transgressor. This study analyzes this ambiguity of the néofantastique on the basis of a number of short stories in the French language by various Belgian and French authors. Key words: Fantasy literature, new fantasy, (néo)fantastique, transgression, taboo, fear, ambiguity, short fiction, the uncanny.